(untitled) (Olhar de Professor, 2025)
The theoretical study is based on the premise that inclusion involves different specialized educational services. The aim was to identify and reflect on actions necessary for the viability of inclusive schooling, through the operationalization of services and conditions necessary for the dissemination of positive social attitudes in the interpersonal relationships of the different social actors involved in the inclusive process. The work was based on legal provisions and a review of the literature, through a general analysis that identified and discussed three specialized educational services: Specialized Educational Assistance (AEE), peer tutoring and co-teaching. The second analysis referred to social attitudes, assessed as favorable or unfavorable to inclusive schooling, since when offering the service, it is necessary to reflect on the attitudinal barriers that exist in interpersonal relationships. It is concluded that initial and continuing teacher training can be a way to implement the services, in a more welcoming and inclusive environment.